ROLE AND MARKET MECHANISM IN ISLAM - Ahmad Zubaidi (El-Arbah: Jurnal Ekonomi, Bisnis Dan Perbankan Syariah, 2022)
The market is a mechanism for the natural exchange of goods and services. Market prices are formed by various factors which then shape the demand for and supply of goods and services. Consumer demand is influenced by many factors, such as price, consumer income, tastes, expectations and level of maslahah. While the producer's supply is also influenced by many factors, such as mashlahah, profit, and price. The interaction between supply and demand that will form the balance point can be changed from the demand or supply side, either as a result of structured deviations or unstructured deviations. Perfect competition market will be able to produce fair prices for sellers and buyers. Therefore, if the market mechanism is disrupted, price justice will not be achieved. Islam places the market in an important position in the economy. And also Islam is very concerned with the concept of fair prices and perfect market mechanisms. So the role of the government is very important to further guarantee the perfect market mechanism activities such as adopting price intervention policies that remain grounded in justice.